2014
DOI: 10.12968/bjcn.2014.19.sup6.s11
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, aetiology and management of wounds in a community care area in Ireland

Abstract: CitationThe prevalence, aetiology and management of wounds in a community care area in Ireland. 2014, Suppl:S11-7 Br J Community Nurs Journal British journal of community nursing Rights Archived with thanks to British journal of community nursing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 25 publications
4
32
2
3
Order By: Relevance
“…Further analysis in a single primary care setting in Ireland resulting in a point prevalence rate of 0.04% (Skerritt and Moore, 2014). A more recent study by Jordan O 'Brien et al (2016) reported that pressure ulcers accounted for 10% of the exiting wound aetiology across acute and community settings.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Further analysis in a single primary care setting in Ireland resulting in a point prevalence rate of 0.04% (Skerritt and Moore, 2014). A more recent study by Jordan O 'Brien et al (2016) reported that pressure ulcers accounted for 10% of the exiting wound aetiology across acute and community settings.…”
Section: Introductionmentioning
confidence: 98%
“…The cost of the nursing time or pressure ulcer prevention/treatment has not as yet been fully and precisely identified. The inclusion of this information is vital if one is to determine the full fiscal impact, and hence analyse the efficacy of various preventative strategies (Skerritt and Moore, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations